Multi-objective optimization based reverse strategy with differential evolution algorithm for constrained optimization problems. Issue 14 (15th August 2015) - Gao, Liang; Zhou, Yinzhi; Li, Xinyu; Pan, Quanke; Yi, Wenchao
Highlights: We rebuilt the model of constrained optimization problems, called reversed model. We developed a comparison strategy based on origin and new model. Difference between usual algorithm and proposed one is discussed. Experimental results show the effectiveness of the proposed algorithm. Abstract: Solving constrained optimization problems (COPs) has been gathering attention from many researchers. In this paper, we defined the best fitness value among feasible solutions in current population as gbest . Then, we converted the original COPs to multi-objective optimization problems (MOPs) with one constraint. The constraint set the function value f ( x ) should be less than or equal to gbest ; the objectives are the constraints in COPs. A reverse comparison strategy based on multi-objective dominance concept is proposed. Compared with usual strategies, the innovation strategy cuts off the worse solutions with smaller fitness value regardless of its constraints violation. Differential evolution (DE) algorithm is used as a solver to search for the global optimum. The method is called multi-objective optimization based reverse strategy with differential evolution algorithm (MRS-DE). The experimental results demonstrate that MRS-DE can achieve better performance on 22 classical benchmark functions compared with several state-of-the-art algorithms.